MEMBANGUN PRODUK PERATURAN DAERAH PERTAMBANGAN MINERAL DAN BATUBARA BERBASIS CITA HUKUM PANCASILA - Sugirman, Andi (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2017)
Building the legal product of a regional regulation on mineral and coal mining is the authority of regional governments. In implementing their authority, they are required to apply Pancasila and embrace the 1945 Constitution of the Republic of Indonesia. Pancasila consisting of five precepts is a legal ideal that should be incarnated in the legal product of a regional regulation on mineral and coal mining. The incarnation of the legal ideal of Pancasila through the legal product of a regional regulation on mineral and coal mining will have the implication on mineral and coal mining management based on the legal ideal of Pancasila. Therefore, building the regional regulation on mineral and coal mining must be based on the normative-juridical aspect as the basis for the making of laws and the theoretical aspect based on the legal ideal of Pancasila.